DRAMATURGY OF LORA ABBAS KATANDUR'S DA'WAH AMONG THE BIKERS IN PAMEKASAN - Moh Toyyib; Arini Fahma Qona’ati; Ikli Nafisah; Moh Hamim Asidiki; Ali Nurdin; Fawaib (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This article analyzes the Dakwah (teach others about the beliefs and practices in Islam) by Lora Abbas Katandur using Erving Goffman Dramaturgy theory. The audience in his dakwah (Mad’u) is the community of bikers in Pamekasan. The data is collected through a case study, and then it is analyzed using textual qualitative method. The result shows that Lora Abbas successfully deliver his Dakwah to the bikers by pointing up the humanistic ideas. His Dakwah is well known as “Sholawatan dan Sarasehan Jalanan” which refers to dakwah conducted on the road. By using this approach, the Da’i (the one who teach Mad’u) also successfully in changing the image of Bikers who tend to be associated with bawl and illegal racing. Morever, the Da’i introduce himself as a role model involving how to speak, how to dress politely, and how to live the life in modesty. This study adds positive constribution to the existing literature about the development of dramaturgy theory in Dakwah. The result of this study is limited to Keywords: Dramaturgi, Dakwah, Da’i, Bikers